Fugitive methane emissions from full-scale wastewater treatment plants: A plant-wide model - Amr Ismail; Amr Mustafa Abdelrahman; Ahmed Elsayed; Mohamed Sherif Zaghloul; Farokh laqa Kakar; John Willis; Allegra da Silva; Domenico Santoro; Tanush Wadhawan; Saba Daneshgar; Ahmed AlSayed; Elsayed Elbeshbishy (Chemical Engineering Journal, 2026)

Multi-level advanced monitoring and quantification of fugitive methane emissions in a full-scale water resource recovery facility - Ahmed Elsayed; Omar Abdelrahman; Mostafa Khalil; Mohamed Sherif Zagloul; Trung Le; Shannon Cavanaugh; John Willis; Farokh Laqa Kakar; Chris Muller; Katherine Bell; Ahmed AlSayed; Elsayed Elbeshbishy (Journal of Environmental Management, 2026)

Quercetin as a promising HIS-C inhibitor and novel therapeutic against antibacterial drug-resistant Acinetobacter baumannii: in vitro and in silico insights - Mohammed Salleh M. Ardawi; Samar A. Badreddine; Muhammad Yasir; Safaa A. Turkistani; Ahmed Afandi; Abdulaziz A. Kimawi; Samah O. Noor; Adhari Alselmi; Salma Mohammed Alsayed; Mada S. Alharthi; Vivek Dhar Dwivedi; Pradeep Sharma; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Drought Tolerance Strategies of Faba Bean Cultivars: Integrated Morphological, Physiological, and Biochemical Responses - Abdelsalam A. Shehab; Ahmed M. Abdelghany; Asmaa Hamoda; Elsayed Sh. Alwakel; Alsayed S. Farouk; Mohamed Ebaid; Sobhi F. Lamlom; Yanjun Guo (Journal of Soil Science and Plant Nutrition, 2026)
Water deficit stress significantly threatens faba bean productivity, highlighting the need to understand cultivar-specific drought tolerance mechanisms to improve breeding efforts. This study aimed to assess the morphological, physiological, and biochemical responses of three faba bean cultivars exposed to different drought levels during the vegetative and flowering stages. Three cultivars (Qidou2, Chenghu10, and Qinghai13) were subjected to different drought levels (35%, 55%, and 100% field capacity) during vegetative and blooming stages. Growth traits, root architecture, gas exchange, antioxidant enzyme activity, cuticular wax composition, and reproductive performance were systematically assessed. Different cultivars showed distinct tolerance patterns. Qidou2 had superior root growth, the highest water-use efficiency at 15.5 µmol CO₂ mmol⁻¹ H₂O, and a flower production tolerance index of about 2.0, indicating strong reproductive resilience. Chenghu10 demonstrated notable adaptability, including a 134% increase in relative intrinsic water-use efficiency under stress and elevated catalase activity at 405.75 U g⁻¹ min⁻¹. Qinghai13 showed moderate tolerance, maintaining steady photosynthesis at 10.33 µmol CO₂ m⁻² s⁻¹ and consistent enzyme activity. Cuticular wax deposition increased sharply during seedling stress (Qidou2: 6.464 to 9.845 µg cm⁻²). Reproductive traits were most stress-sensitive; for example, Qidou2 did not produce pods under severe drought despite vigorous growth. Overall, the findings highlight that coordinated responses across root architecture, physiology, metabolism, and protective barriers underpin drought adaptation. The diverse strategies identified across cultivars, from conservative water use to enhanced metabolic efficiency, provide valuable targets for breeding drought-resilient faba beans.

How operational strategies influence nitrogen removal and nitrous oxide emissions: Insights from a full-scale wastewater treatment plant - Mostafa Khalil; Marwan Alsaleh; Ahmed Elsayed; Hussein Aqeel; Ahmed Al-Omari; Shannon Cavanaugh; Farokh Laqa Kakar; Katherine Bell; Allegra K. da Silva; Jose Porro; Ahmed AlSayed; Steven N. Liss; et al. (Journal of Environmental Management, 2026)

Phytochemical insights and hepatoprotection evaluation of Heliotropium arbainense: Analyzing gene expression and therapeutic potential - Alsayed E. Mekky; Albayoumi A. Fouda; Osama Mohammad Mohammad Abdelhay; Kamal Rady Mohammed; Mohamed Arafat Mohamed Mansour; Mohamed A.M. El-Tabakh; Abeer Mahmoud Mohammad; Amani Alhejely; Taiseer Ahmed Shawky; Eslam S. Abdelmouty; Mohamed Khedr; Mahmoud Radwan; et al. (South African Journal of Botany, 2025)

Recent Advances in Applying Nanobubbles for Enhanced Anaerobic Digestion: Fundamentals, Challenges, and Future Prospects - Alsayed Mostafa; Ahmed Elsayed; Rasha Maal-Bared; Elsayed Elbeshbishy; Bipro Ranjan Dhar (BioEnergy Research, 2025)

From process fundamentals to engineering perspectives: A technical review on in-situ biogas upgrading via the hydrogenotrophic methanogenesis pathway - Amr Mustafa Abdelrahman; Noura Abdelrazec; Ahmed AlSayed; Farokh Laqa Kakar; Chris Muller; Katherine Y. Bell; Elsayed Elbeshbishy (Biomass and Bioenergy, 2025)

Geochemistry and tectonic evolution of Neoproterozoic Wadi Kid Dokhan volcanics, Southeast Sinai, Egypt - Hatem M. El-Desoky; Ahmed M. Abdel-Rahman; Wael Fahmy; Islam M. Alsayed; Hamada El-Awny; Ahmed E. Khalil; Ahmed Eraky (Mineralogy and Petrology, 2025)

Illuminating bioprocess responses to metal-based nanoparticles addition along hydrogen and methane production pathways: A review - Ahmed Elreedy; Mohamed Elsamadony; Alsayed Mostafa; Johannes Gescher; Omar Y. Abdelaziz; Manabu Fujii (Bioresource Technology, 2025)

Mineralogic and geochemical characteristics of Duwi Formation black shale, Safaga District, Central Eastern Desert, Egypt - Hatem M. El-Desoky; Islam M. Alsayed; Esam A. Abd El Gawad; Ahmed Y. Abd El-Rahman; Ibrahim S. Abdullah (Carbonates and Evaporites, 2024)

Advances in GHG emissions modelling for WRRFs: From State-of-the-Art methods to Full-Scale applications - Mostafa Khalil; Ahmed AlSayed; Ahmed Elsayed; Mohamed Sherif Zaghloul; Katherine Y. Bell; Ahmed Al-Omari; Farokh Laqa Kakar; Dwight Houweling; Domenico Santoro; Jose Porro; Elsayed Elbeshbishy (Chemical Engineering Journal, 2024)

An integrated feature selection and hyperparameter optimization algorithm for balanced machine learning models predicting N2O emissions from wastewater treatment plants - Mostafa Khalil; Ahmed AlSayed; Yang Liu; Peter A. Vanrolleghem (Journal of Water Process Engineering, 2024)

Manipulating dissolved oxygen concentration to control the partitioning between carbon oxidation and redirection in the A-stage high rate activated sludge process - Ahmed AlSayed; Moomen Soliman; Ahmed ElDyasti (Journal of Water Process Engineering, 2024)

Selenium Nanoparticles Modulate Steroidogenesis-Related Genes and Improve Ovarian Functions via Regulating Androgen Receptors Expression in Polycystic Ovary Syndrome Rat Model - Ahmed B. E. Abdallah; Mohammed A. El-Ghannam; Azza A. Hasan; Lamiaa G. Mohammad; Noura M. Mesalam; Radwa M. Alsayed (Biological Trace Element Research, 2023)
Polycystic ovary syndrome (PCOS) occurs during the reproductive period in women and is characterized by reproductive, endocrine, and metabolic disorders. Androgen plays a decisive role in its pathogenesis due to the interaction between hyperandrogenism and insulin resistance, which might be improved by selenium nanoparticles (SeNPs). The present study aimed to clarify the effect of SeNPs on androgen synthesis and action in the PCOS model and the resulting effect on ovarian function. Fifty-five 7-week-old female albino rats (90–105 g) were divided equally into five groups: control (C), fed a standard diet for 11 weeks; high-fat diet (HFD) group, fed HFD for 11 weeks; HFD and letrozole (L) (HFD + L), fed HFD for 11 weeks and administrated orally with L, at a daily dose of 1 mg/kg BW, for three weeks from the 7th to 9th week of the trial; HFD + L + 0.1SeNPs and HFD + L + 0.2SeNPs groups, treated the same as HFD + L group and orally gavaged SeNPs at daily doses of 0.1 and 0.2 mg/kg BW, respectively, during the last 14 day of the experiment. Daily determination of estrous cycle was performed, and at the end of the experimental period, BMI, serum glucose, insulin, HOMA-IR, lipid profile, sex hormones, TNF-α, IL6, oxidative stress biomarkers, ovarian mRNA expression of different proteins and enzymes involved in steroidogenesis, pathological examination, and immunohistochemical staining for androgen receptor (AR) were evaluated. Treatment of SeNPs restored estrous cyclicity, decreased BMI, and insulin resistance, improved dyslipidemia, reduced serum testosterone, and improved ovarian histopathology in PCOS rats. Furthermore, the anti-inflammatory and antioxidant impacts of SeNPs were remarkably noticed. Administration of SeNPs decreased androgen synthesis and expression of ovarian AR protein by decreasing the mRNA expression of STAR, Cyp11A1, Cyp17A1, and HSD17B3 and increasing the expression of Cyp19α1 . Conclusively, SeNPs decreased androgen synthesis and blocked the vicious circle initiated by excessive androgen secretion via decreased AR expression. Thus, it may effectively treat PCOS cases by eliminating its reproductive, endocrine, and metabolic dysfunctions.

The A-stage process to promote bioflocculation and microbial storage for carbon redirection: current perspectives and future research directions - Ahmed AlSayed; Moomen Soliman; Ahmed Eldyasti (Reviews in Environmental Science and Bio/Technology, 2023)

Bioelectrochemical system for enhancing anaerobic digestion of pharmaceutical-containing domestic wastewater - Alsayed Mostafa; Mohamed Elsamadony; Tarek E. Khalil; Amel F. Elhusseiny; Ahmed Tawfik; Manabu Fujii; Ali El-dissouky; Deepak Pant (Chemosphere, 2023)

Machine learning for modeling N2O emissions from wastewater treatment plants: Aligning model performance, complexity, and interpretability - Mostafa Khalil; Ahmed AlSayed; Yang Liu; Peter A. Vanrolleghem (Water Research, 2023)

The synergy between serious parasitic pathogens and bacterial infestation in the cultured Nile tilapia (Oreochromis niloticus): a severe threat to fish immunity, causing mass mortality and significant economic losses - Mahmoud Radwan; Mahmoud A. El-Sharkawy; Ahmed N. Alabssawy; Sara F. Ghanem; Amaal Mohammadein; Jamila S. Al Malki; Asma W. Al-Thomali; Eman A. Manaa; Ragab A. Soliman; Shahd Yassir; Alsayed E. Mekky; Mansour A. E. Bashar; et al. (Aquaculture International, 2023)

Mechanistic assessment reveals the significance of HRT and MLSS concentration in balancing carbon diversion and removal in the A-stage process - Ahmed AlSayed; Moomen Soliman; Ahmed ElDyasti (Journal of Environmental Management, 2023)

Seasonal Variability in Ocean Heat Content and Heat Flux in the Arabian Gulf - Afnan Y. Alsayed; Mohammed A. Alsaafani; Abdullah M. Al-Subhi; Turki M. Alraddadi; Ahmed M. Taqi (Journal of Marine Science and Engineering, 2023)
This study aimed to evaluate the seasonal variability in surface heat content in the Arabian Gulf (AG) based on hydrographic data. The ocean heat content (OHC) was initially estimated from surface to maximum depth (75 m) to show the seasonal variability, where the seasonal temperature reaches to that depth. Then OHC was re-estimated from the surface to a depth of 35 m, which represents the average depth of AG, to obtain accurate horizontal distributions. Results showed that during winter, the northern part of AG experiences the lowest OHC compared to the southeastern part. The monthly spatial average implies that the highest OHC of AG water was in September and October, while the lowest heat content was found in February and March. However, the OHC horizontal distributions were almost the same for the entire gulf during summer. In general, there was increasing in the OHC in the southeast region of the gulf. OHC anomalies are concentrated in the northern region of the AG, while the southeastern part near the Strait of Hormuz has the lowest values. Regarding heat flux, the highest heat gains were during spring, while the highest loss was in autumn. The water exchange between the AG and the Indian Ocean through the Strait of Hormuz may play a major role in the seasonal variability in OHC.

Economic adaptive traffic signal system: design and operation - Alsayed Alsobky; Ahmed Saeed; Ibrahim El-Dimeery (Innovative Infrastructure Solutions, 2022)

Cytotoxic and anti-diabetic potential, metabolic profiling and insilico studies of Syzygium cumini (L.) Skeels belonging to family Myrtaceae - Seham Salah Eldin Elhawary; Amira kamal Eldin Elmotayam; Doaa kamel Alsayed; Eman Maher Zahran; Merivat Ahmed Fouad; Amany Ameen Sleem; Hanan Elimam; Mohamed H. Rashed; Alaa M. Hayallah; Anber F. Mohammed; Usama Ramadan Abdelmohsen (Natural Product Research, 2022)

Quantile Regression to Tackle the Heterogeneity on the Relationship Between Economic Growth, Energy Consumption, and CO2 Emissions - Ahmed R. M. Alsayed; Zaidi Isa; Sek Siok Kun; Giancarlo Manzi (Environmental Modeling & Assessment, 2020)

Harvesting zero waste from co-digested fruit and vegetable peels via integrated fermentation and pyrolysis processes - Mohamed Soltan; Mohamed Elsamadony; Alsayed Mostafa; Hanem Awad; Ahmed Tawfik (Environmental Science and Pollution Research, 2019)

Sustainable biogas mitigation and value-added resources recovery using methanotrophs intergrated into wastewater treatment plants - Ahmed AlSayed; Ahmed Fergala; Ahmed Eldyasti (Reviews in Environmental Science and Bio/Technology, 2018)

Dual mTORC1/mTORC2 blocker as a possible therapy for tauopathy in cellular model - Mohamed Salama; Mahmoud Elhussiny; Alshimaa Magdy; Ahmed G. Omran; Aziza Alsayed; Ramy Ashry; Wael Mohamed (Metabolic Brain Disease, 2018)

The landscape of genetic diseases in Saudi Arabia based on the first 1000 diagnostic panels and exomes - Dorota Monies; Mohamed Abouelhoda; Moeenaldeen AlSayed; Zuhair Alhassnan; Maha Alotaibi; Husam Kayyali; Mohammed Al-Owain; Ayaz Shah; Zuhair Rahbeeni; Mohammad A. Al-Muhaizea; Hamad I. Alzaidan; Edward Cupler; et al. (Human Genetics, 2017)